78.4k views
5 votes
Given g(x)=−2x2+1, find the indicated values: g(−3)

2 Answers

5 votes

Question:

g(x) = -2x^2 + 1 if g(-3)

Steps:

1. plug 3 in the x

-3(-3)^2 + 1

Exponent always come before you distribute so,

2. Simplify,

-3(9) + 1

-27 + 1

= -26


Hope that helped!!

~Shane

User Sfuerte
by
5.4k points
0 votes

g(x) = -2x² + 1

g(-3) = -2(-3)² + 1

= -2(9) + 1

= -18 + 1

= -17

Answer: -17

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.